Analytical solution of temperature distribution in a nonuniform medium due to a moving laser beam and a double beam scanning strategy in the selective laser melting process - Loh, Loong-Ee (2019)
Selective laser melting (SLM) has received increasing attention in recent years as an innovative manufacturing technique. The present SLM process only uses a single laser beam to melt and consolidate the powder, which may result in excessive evaporation. In this paper, a double beam scanning strategy is investigated in which the first laser beam preheats the powder just below the sintering point while the second laser beam completely melts the powder. An analytical solution on the temperature distribution heated by a moving laser beam in the powder-bulk domain is derived and is used to determine the critical radius of the first laser beam. The single and double beam scanning strategies are compared numerically and it is found that double beam scanning can effectively reduce material evaporation and increase the amount of powder melted in the SLM process.